2015
DOI: 10.11646/zootaxa.4039.1.7
|View full text |Cite
|
Sign up to set email alerts
|

New Acotylea (Polycladida, Platyhelminthes) from the east coast of the North Atlantic Ocean with special mention of the Iberian littoral

Abstract: Polyclad species diversity, although generally well known for European North Atlantic waters, is nearly unknown for the Iberian Peninsula. The "Ría de Arousa", located on the Atlantic coast of Galicia (Spain), is a place where many positive biological factors for species biodiversity converge. Therefore, it is an ideal location to study polyclad diversity. This research, which describes new records and new species, contributes to the knowledge of the distribution of Polycladida (Platyhelminthes), particularly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…As well, Bahia et al (2017) found that Hoploplana was sister to Planocera, nested within Stylochoidea. Additionally, Noreña et al (2015) noticed that Hoploplana possess an atypical granular prostatic gland with the ejaculatory duct and the granular secretions packed at the beginning of the stylet. Our results argue for a distinction between the prostatic vesicle of leptoplanoideans and that of Hoploplana, and the inclusion of the latter in Stylochoidea.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As well, Bahia et al (2017) found that Hoploplana was sister to Planocera, nested within Stylochoidea. Additionally, Noreña et al (2015) noticed that Hoploplana possess an atypical granular prostatic gland with the ejaculatory duct and the granular secretions packed at the beginning of the stylet. Our results argue for a distinction between the prostatic vesicle of leptoplanoideans and that of Hoploplana, and the inclusion of the latter in Stylochoidea.…”
Section: Discussionmentioning
confidence: 99%
“…The samples were progressively dehydrated and embedded in paraplast and serially sectioned sagittally at intervals of 7 μm and stained with AZAN (trichrome staining method). Detailed morphological descriptions for most of the species used in this study can be found in Brusa and Damborenea (2011), Marquina et al (2014aMarquina et al ( , b, 2015 and Noreña et al (2014Noreña et al ( , 2015.…”
Section: Morphological Analysismentioning
confidence: 99%
“…Tyrrhenian Sea (Lang 1884); Ria de Arosa, Spain (Noreña et al 2015). This species has also been cited by DORIS (Données d'Observations pour la Reconnaissance et l'Identification de la faune et la flore Subaquatiques) for the English Channel and the North Sea, from the south of the United Kingdom to the Bay of Biscay (Spain) (http://doris.ffessm.fr/Especes/Prostheceraeus-moseleyi-Planaire-tachetee-716).…”
Section: Distributionmentioning
confidence: 96%
“…6I). (Novell 2003); Mar Menor, Murcia, Spain (Marquina et al 2014); Ría de Arousa, Galicia, Spain (Noreña et al 2015); Cape Verde (Laidlaw 1906); Rufisque, Senegal (Palombi 1939).…”
Section: New Recordsmentioning
confidence: 99%
See 1 more Smart Citation